OPTIMIZING STUDENTS' CRITICAL THINKING AND NUMERACY LITERACY SKILLS THROUGH TASK-BASED LEARNING: AN EXPERIMENTAL STUDY - Bernadetha Rizki Kaize; Ni Nyoman Rediani; Syahfitriani Br Ginting (Indonesian Journal of Educational Development (IJED), 2024)
The suboptimal critical thinking and numeracy literacy skills among students, which can impact the quality of human resources, is the reason this research aims to examine the effects of task-based learning on critical thinking and numeracy literacy. The research method used is a quasi-experimental design with a nonequivalent posttest-only control group design. The focus of this study is on PGSD (Elementary School Teacher Education) students enrolled in numeracy literacy courses, with a total of 120 students divided into 4 classes. Data collection was conducted through tests. Data analysis included descriptive analysis and inferential statistical analysis, with inferential analysis performed using the MANOVA (Multivariate Analysis of Variance) method. The results of the study indicate that the implementation of the task-based learning method has a significant impact both simultaneously and partially on critical thinking and numeracy literacy skills. This is evident from the higher average scores observed in the experimental class that applied this method, compared to the control class that did not use it. Therefore, it is recommended that the task-based learning method be used as a solution to address the issues related to low critical thinking and numeracy literacy skills.